Phosphorus : an outline of its chemistry, biochemistry, and technology - Corbridge, D. E. C. (Studies in inorganic chemistry, 1980)
Studies in Inorganic Chemistry 2, Phosphorus: An Outline of Its Chemistry, Biochemistry and Technology, Second Edition deals with the organic, inorganic, biochemical, physical, environmental, and technical aspects of phosphorus chemistry.